RELEVANSI PERSYARATAN PEWARGANEGARAAN BERDASARKAN PERMOHONAN DENGAN PEWARGANEGARAAN BERDASARKAN PEMBERIAN NEGARA MENURUT UNDANG-UNDANG NOMOR 12 TAHUN 2006 TENTANG KEWARGANEGARAAN REPUBLIK INDONESIA - Purnama Sari Wijaya, Megawati; Suantra, I Nengah; Nurmawati, Made (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 07, November 2013)
Principally, for establishing of the independent country must have some requirementssuch as: the definitive area, the definitive people or community, a sovereign government; thesethree conditions is a unity that can not be divided. Getting Indonesian citizen through anapplication must satisfy the conditions under Article 9 of Act Number. 12 / 2006 about TheRepublic of Indonesia Citizenship, the other hand Indonesian Citizenship obtained by giving thestate specified in Article 20 of The Act Number12 / 2006. Correlation of law between citizenshipgetting by citizenship application with citizenship, which it is getting by giving the state is inArticle 9 point d and also explanation of Article 20 The Act Number 12 / 2006 about TheIndonesia Republic Citizenship. The main law issue of the correlation is related to the terms ofcitizenship based on giving the state and the meaning of one of the terms, i.e the greatachievment, which it is the terms to get the citizhen of The Indonesia Republic by getting of thestate.
Keywords: Citizen, Relevance, Great Achievement